THE “RIGHT” IN THE CHILEAN POPULAR FRONT: A STUDY OF “SEVERAL PERIODS”, 1932-1948. - Rubio Apiolaza, Pablo (Revista de Historia Social y de las Mentalidades, 2011)
Between 1938 and 1952, most of the Chilean  governments implement policies put center- left. Greater political democracy and social  rights, plus an economic strategy linked to  the state-led industrialization seem to be the  main areas of policy drivers of the period.  However, in this scenario, the traditional  right-composed of the Conservative and  Liberal, became a protagonist who can not  be underestimated. The hypothesis advanced  is that the right in Chile is an active field and  deep divisions, which prevented him from  being a majority in Chile at that time. These  hypotheses systematize and fall within a larger  historical debate.
Keywords: political; right-front; commitment; popular-state